Correction to: Social and environmental determinants of child health in Mongolia across years of rapid economic growth: 2000-2010 - Nehal Joshi; Bolormaa Bolorhon; Indermohan Narula; Shihua Zhu; Semira Manaseki-Holland (BMC, 2018)
Abstract Unfortunately, after publication of this article [1], it was noticed that an error during the production process resulted in an incorrect author name. The author Semira Manaseki-Holland is incorrectly displayed as Semira Manaseki-Hollan. The full, corrected author list can be seen above.